PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS DISCOVERY LEARNING BERBANTUAN GEOGEBRA PADA GEOMETRI KELAS IV SD - Mira Nopitria Nopitria; Agus Susanta; Irwan Koto (Jurnal Kajian Pendidikan Dasar (Kapedas), 2022)
The aims of study is to describe how to develop, the feasibility and student responses to the development of discovery learning-based LKPD integrated with Geogebra in Geometry grade IV elementary school. This research includes research and development (Research and Development). The model used is Borg and Gall, namely: (1) Data and Information collection, (2) Planning, (3) initial product development, (4) Initial Field Test, (5) Product Revision, (6) Main Field Test, (7) Product Revision (8) Operational Field Trial (9) Final Product Revision, (10) Dissemination and distribution. In this development research, the researcher limits from 10 steps to 5 steps. The subjects in this study were teachers and fourth grade students of SD Negeri 01 Pendopo. The result of this research isthe LKPD of Mathematics based on Discovery Learning assisted by Geogebra is valid based on expert judgment on three aspects of feasibility. Feasibility of material with validity 0.87, feasibility of language with validity 0.94, and feasibility of graphic 0.91. 99% student response, and 95% teacher response. These results indicate that the Geogebra-assisted Discovery Learning-based Mathematics LKPD is feasible and gets a very positive response from students.